ACTIVITIES OF THE ADMINISTRATION OF THE FEDERAL SERVICE FOR SURVEILLANCE ON CONSUMER RIGHTS PROTECTION AND HUMAN WELL-BEING IN THE PRIMORSKY KRAI IN CONNECTION TO THE SITUATION AT THE FUKUSHIMA NPP - D. V. Maslov; M. V. Polyakova; I. A. Markova; S. I. Morozova; G. G. Laukhina (Радиационная гигиена, 2015)
The article describes activities of the Administration of the Federal Service for Surveillance on Consumer Rights Protection and Human Well-being in the Primorsky Krai on organization of works in conditions of the radiation accident at the Fukushima NPP directed at providing of radiation protection of the population of the region. It presents results of radiation situation monitoring that was implemented by the Federal Organization for Public Health “Center of Hygiene and Epidemiology in the Primorsky Krai”.